A time series analysis of aggregate consumption function for Pakistan - Islam, Tanweer; Zafar, Zakia (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
Aggregate Consumption, being an important part of National Income Accounts, has been intensively researched in macroeconomics. Aggregate consumption and aggregate savings have powerful influence on an economy’s long-term productive capacity and capture the macroeconomic fluctuations and business cycles more appropriately. This interest reflects the belief that the structural forms of consumption functions and theories are a key to solve many business cycle issues. This study provides a time series analysis of aggregate consumption function for Pakistan by using a quarterly data from 1973(1) to 2010(4). The DHSY’s error correction and Hall’s random walk models are empirically tested. The data validate the application of both methodologies in estimating the aggregate consumption function. Hall’s martingale hypothesis also holds showing that current consumption is a good predictor of future consumption in Pakistan. In the context of Pakistan, 86% of the income has been consumed in the long run while the rest is saving. Inflation is unanticipated but is not accelerating. The data provide enough evidence to reject the price homogeneity hypothesis, however we are unable to reject the hypothesis of the unit elasticity of income. The Mankiw and Campbell test concludes that there are 49% of consumers who are backward looking while 51% follow permanent income hypothesis and are forward looking
Argumenta Oeconomica, 2017, Nr 1 (38), s. 243-255
Keywords: random walk; error correction; martingale; price homogeneity